The Economic Significance of the Hadith “Waḍʿ wa Taʿajjul” and Its Contemporary Applications - Faisal Mohammed Al-Ajmi (Islamic Sciences Journal, 2026)
The Book revealed to the Prophet Muhammad (peace and blessings be upon him) is a miracle that humanity has been unable to replicate, due to its harmonious texts. It arrived with the most concise expression, the deepest meaning, and the most enduring impact. To illustrate this, I have attempted to convey and clarify the impact of sound planning and management in governance through the story of Prophet Joseph (peace be upon him), which serves as an example of systematic planning. In this story, Joseph (peace be upon him) interpreted the king's dream and devised a plan to address the impending crisis. This plan involved investing the harvest during the seven fertile years and storing grain in the ears to prevent waste. It also highlights the role of patience in achieving goals and its contribution to governance, as well as how Prophet Jacob (peace be upon him) planned to overcome a problem..